2017
DOI: 10.1111/jan.13317
|View full text |Cite
|
Sign up to set email alerts
|

The effects of nursing preceptorship on new nurses’ competence, professional socialization, job satisfaction and retention: A systematic review

Abstract: Preceptorship can improve new nurses' nursing competence; however, more studies are needed to ascertain its effects on new nurses' retention rates, job satisfaction and professional socialization to promote nursing care quality and resolve nursing shortages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
73
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(82 citation statements)
references
References 29 publications
9
73
0
Order By: Relevance
“…According to the density maps of the title and abstract terms, we observed greater density in the term “patient.” Next, with lower density, we observe the term “student” and finally, with a lower density, the term “hospital” appears. In line with our results, we found other studies research these terms (Ke, Kuo, & Hung, ; Li et al., ; Martín‐Del‐Río, Solanes‐Puchol, Martínez‐Zaragoza, & Benavides‐Gil, ). It′s important for nursing research, professionals, managers, and nursing professors in everywhere, to know which are the journals with most published articles or articles cited, the most relevant institutions, countries, authors, most cited articles, as well as getting to know the most relevant academic teams (Mantzoukas, ).…”
Section: Discussionsupporting
confidence: 93%
“…According to the density maps of the title and abstract terms, we observed greater density in the term “patient.” Next, with lower density, we observe the term “student” and finally, with a lower density, the term “hospital” appears. In line with our results, we found other studies research these terms (Ke, Kuo, & Hung, ; Li et al., ; Martín‐Del‐Río, Solanes‐Puchol, Martínez‐Zaragoza, & Benavides‐Gil, ). It′s important for nursing research, professionals, managers, and nursing professors in everywhere, to know which are the journals with most published articles or articles cited, the most relevant institutions, countries, authors, most cited articles, as well as getting to know the most relevant academic teams (Mantzoukas, ).…”
Section: Discussionsupporting
confidence: 93%
“…Findings from this study show that many factors influence the com- NGNs' competencies, which has been corroborated by other recent systematic reviews (Ke, Kuo, & Hung, 2017;Whitehead et al, 2013).…”
Section: Discussionsupporting
confidence: 89%
“…These authors identified 30 studies analysing the effectiveness of such programmes on the deployment of competencies, self‐confidence, levels of stress and anxiety, and job satisfaction of NGNs. They concluded that these programmes have a positive influence on all indicators, including on the deployment of NGNs’ competencies, which has been corroborated by other recent systematic reviews (Ke, Kuo, & Hung, ; Whitehead et al, ).…”
Section: Discussionsupporting
confidence: 53%
“…Nurses at this level of practice may be challenged by patient deterioration in and of itself and may not be equipped to also address novice needs. Consistent with Benner's theory, a recent systematic review revealed that preceptors’ clinical work experience of three or more years was a significant factor in improving novice nurse competency development (Ke et al., ). This finding should lend perspective to nurse administrators and educators responsible for preceptor selection and support.…”
Section: Discussionmentioning
confidence: 89%
“…Specifically, the preceptorship component has been identified as critical to novices' transition to complex work environments (Della Ratta, 2016;Moore & Cagle, 2012). The most common preceptorship model is that of a fixed preceptor/preceptee dyad who work together one-on-one for a period of 1-3 months (Ke, Kuo, & Hung, 2017). Preceptors serve as clinical experts, provide day-to-day support and instruction for novices and evaluate their development and competence.…”
Section: Introductionmentioning
confidence: 99%